Use of an Extracorporeal Centrifugal Pump with the Berlin Cannulas. Issue 5 (July 2019) - Chen, Peter C.; Zea-Vera, Rodrigo; Burgman, Cole; McKenzie, E. Dean; Elias, Barbara; Adachi, Iki
Abstract : The Berlin EXCOR ventricular assist device has become a standard treatment in pediatric bridge to transplantation. Despite its increased use in pediatric heart failure, the patient population supported with this technology continues to suffer from hematologic issues such as postoperative hemorrhage and neurologic dysfunction secondary to thrombotic events. Finding a balance between hemorrhagic and thrombotic risks in the acute postoperative period poses a significant challenge. In this report, we describe our approach using a temporary centrifugal pump connected to cannulas designed for the Berlin EXCOR ventricular assist device. We believe that the interim use of an extracorporeal centrifugal pump allows time for hemodynamic stability, limits the hemorrhagic risks, and provides relevant hemodynamic information before conversion to the Berlin EXCOR.